Strategi Manajemen Kurikulum Dalam Peningkatan Kualitas Pendidikan: Studi kasus di MTS Nurul Islam Desa Alai - Hoirotul Hasanah; Siti Fatimah; Nadhea Pratiwi; Maisin Dila Saputri (Jurnal Budi Pekerti Agama Islam, 2024)
Curriculum management is a regulatory activity that includes planning, organizing, implementing and supervising or evaluating so that educational programs can run well and in sync with predetermined goals. From the background above, the author formulates the title "Curriculum Management Tactics for Improving the Quality of Education." The problem formulation in this thesis is how curriculum management issues in an effort to improve the quality of education at MTS Nurul Islam Alai Village and how the art of curriculum management improves quality. education at MTS Nurul Islam Alai Village. Meanwhile, for the analysis, the author uses qualitative narrative analysis techniques, namely in the form of written or verbal data from people and observed behavior so that in this case the author tries to conduct real research. As a result of the research that the author conducted, it is known that the problem with curriculum management in efforts to improve the quality of education at MTS Nurul Islam Alai Village is a lack of time allocation, too many students in one class, and a lack of educational infrastructure.